The technician - Asher, Neal L., 1961- (Asher, Neal L., 1961- Novels of the Polity, 2020)
The Theocracy has been dead for twenty years, and the Polity rules on Masada. But the Tidy Squad consists of rebels who cannot accept the new order. Their hate for surviving theocrats is undiminished, and the iconic Jeremiah Tombs is at the top of their hitlist. Escaping his sanatorium Tombs is pushed into painful confrontation with reality he has avoided since the rebellion. His insanity must cured, because the near mythical hooder called the Technician that attacked him all those years ago, did something to his mind even the AIs fail to understand. Tombs might possess information about the suicide of an entire alien race. The war drone Amistad, whose job it is to bring this information to light, recruits Lief Grant, an ex-rebel Commander, to protect Tombs, along with the black AI Penny Royal, who everyone thought was dead. The amphidapt Chanter, who has studied the bone sculptures the Technician makes with the remains of its prey, might be useful too. Meanwhile, in deep space, the mechanism the Atheter used to reduce themselves to animals, stirs from slumber and begins to power-up its weapons.